2016
DOI: 10.1055/s-0042-107795
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein (TSPO) Expression in Platelets of Depressed Patients Decreases during Antidepressant Therapy

Abstract: ▼Introduction: A promising candidate in the field of pharmacological treatment options regarding major depressive disorder (MDD) is the mitochondrial translocator protein (18 kDa) (TSPO). TSPO is crucial for neurosteroid synthesis, which is in turn important for the regulation of emotions. It has already been shown that TSPO expression in platelets of depressed patients is reduced compared to healthy subjects. Methods: We measured TSPO levels in platelets of 37 depressed patients before and after 6 weeks of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…As this study did not demonstrate changes in TSPO expression in microglia in vivo after irradiation, this suggests that the reduction in TSPO seen after LDIR was primarily from cells which constitutively express TSPO rather than from inducible expression. This is consistent with previous studies which have demonstrated a downregulation in TSPO expression from baseline in several neurological and psychiatric disorders, including PTSD ( Gavish et al, 1996 ), depression ( Chelli et al, 2008 ; Sarubin et al, 2016 ), and reduced TSPO ligand binding in PET imaging of recent onset schizophrenia ( Notter et al, 2018a ), despite the induction of systemic cytokine immune responses. We previously speculated that the reduced levels of TSPO that have sometimes been demonstrated in molecular imaging studies under certain subtle disease states reflect changes in vascular endothelial cells, which we found to have widely distributed, albeit low-level, expression of TSPO across the brain ( Betlazar et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…As this study did not demonstrate changes in TSPO expression in microglia in vivo after irradiation, this suggests that the reduction in TSPO seen after LDIR was primarily from cells which constitutively express TSPO rather than from inducible expression. This is consistent with previous studies which have demonstrated a downregulation in TSPO expression from baseline in several neurological and psychiatric disorders, including PTSD ( Gavish et al, 1996 ), depression ( Chelli et al, 2008 ; Sarubin et al, 2016 ), and reduced TSPO ligand binding in PET imaging of recent onset schizophrenia ( Notter et al, 2018a ), despite the induction of systemic cytokine immune responses. We previously speculated that the reduced levels of TSPO that have sometimes been demonstrated in molecular imaging studies under certain subtle disease states reflect changes in vascular endothelial cells, which we found to have widely distributed, albeit low-level, expression of TSPO across the brain ( Betlazar et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…It plays an important role in neurosteroid synthesis and in systemic endocrine regulation, with implications in the pathophysiology of immune, inflammatory, neurodegenerative, neoplastic and psychiatric diseases 113 . Interestingly, Sarubin et al 114 investigated the effects of antidepressant treatment on TSPO expression levels in platelets obtained from 37 patients suffering from MDD, analysing TSPO levels in depressed patients before and after 6 weeks of antidepressant treatment. A significant change in TSPO levels over 6 weeks of treatment was observed within the complete sample of MDD patients.…”
Section: Treatmentmentioning
confidence: 99%
“…Since the semiquantitative parameter SUV, which does not account for changes in peripheral metabolism of the radioligand [13], did not exhibit a decrease in uptake after blocking of TSPO, we investigated if we could use a pseudo-reference agent as in the brain where the cerebellum has been used [14]. We used both blood and cancellous bone, both of which contain TSPO [15,16] as pseudo-reference region as an estimate specific [ 11 C]PBR28 tissue uptake. We found that like V T , a decrease in SUVr 50-70 blood and SUVr 50-70 bone was observed after TSPO blocking with XBD-173 was noted with a decrease, indicating that both SUVr 50-70 blood and SUVr 50-70 bone could be used to quantify [ 11 C]PBR28 uptake.…”
Section: Discussionmentioning
confidence: 99%